Retraction of: Parra, A., & Giménez Amarilla, P. (2017). Anomalous/paranormal experiences reported by nurses in relation to their patients in hospitals. Journal of Scientific Exploration, 31(1), 11–28. - Erickson, Kathleen E (Journal of Scientific Exploration, 2021)
The Journal of Scientific Exploration is retracting this article because of multiple instances of plagiarism, with no attribution (no quotation marks used, no text citations). The first source is not cited and does not appear in the References. The second source is cited once but not related to the plagiarized text, and it does appear in the References list.